Ozone Processing of Peach Juice: Impact on Physicochemical Parameters, Color, and Viscosity - Jaramillo Sánchez, Gabriela Maribel (2018)
The impact of gaseous ozone on pH, °Brix, titratable acidity, and optical and rheological properties of fresh squeezed peach juice was investigated. Peach juice was exposed to ozone (0.06–2.48 g. L−1) in a bubble column at 20 ± 1 °C. Nonsignificant or slight changes in pH, °Brix, and titratable acidity were found during ozonation. Lightness (L*) slightly decreased in the first minute of O3 exposure and then remained practically constant, while a* parameter slightly increased in all treated samples. L* and a* parameters as well as Browning Index values reflected a slight increase in browning in ozonized juices. All juices, treated and untreated, exhibited non-Newtonian flow characteristics with pseudoplastic behavior. Significant reductions in apparent viscosity and a trend toward Newtonian flow as O3 treatment time increased were observed for ozonized juices. The Power Law model was suitable to fit rheological data.